(3JMaI GdJQc ajef jLH Cf jYed aj Gdedcs - (3GdWQShSj , EHQGgje Hf Ydj Hf CMeO Hf YHO GdhGMO Hf YHO GdefYe, fLe GdOjf GdWQShSj,J (B758 (3g` s
(3ChdgG (B:s
(3eGdc Gdedc QH Gdedhc hHYO aEf Gddg JYGdi LYd MaX fXGe GdCfGe HGdSdWGf hQCjJ Cf ef GdhGLH HPGd GdfUjMI dg HbOQ GdEecGf GdaUd GdChd ai HjGf UMI GdSdWfI GdJQc s
(3BNQgG (B:s
(3hjchf ddSdWGf dCf GdYHO eG jedc dehdGg hdGTc Gfg jJejR Yf HbjI GdLjT hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B62s
Keywords: (3GdSjGSI hGdGLJeGYs